1989
DOI: 10.1182/blood.v73.7.1909.1909
|View full text |Cite
|
Sign up to set email alerts
|

Detection of major histocompatibility complex class I-restricted, HIV- specific cytotoxic T lymphocytes in the blood of infected hemophiliacs

Abstract: Major histocompatibility (MHC)-restricted, human immunodeficiency virus type one (HIV-1)-specific, cytotoxic T lymphocytes (CTLs) were detected in the peripheral blood mononuclear cells (PBMCs) of HIV-1-infected individuals. Using a system of autologous B and T lymphoblastoid cell lines infected with recombinant vaccinia vectors (VVs) expressing HIV-1 gene products, we were able to detect HIV-1-specific cytolytic responses in the PBMCs of 88% of HIV-1-seropositive hemophiliac patients in the absence of in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
1

Year Published

1990
1990
1999
1999

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(31 citation statements)
references
References 34 publications
1
29
1
Order By: Relevance
“…The intensities of FIV-specific cytotoxic responses by PBMC with or without a brief stimulation with the T-cell mitogen ConA and IL-2 were lower than those reported for PBMC or ConA blasts of HIV-seropositive humans (14,19,22,30,46,48) or SIV-infected primates (26-28). In addition, we were unable to detect cytotoxic T-cell responses in lymphoblasts sampled before 7 weeks postinfection, whereas SIV-specific cytotoxicity mediated by PBMC was detected as early as 2 weeks after infection of macaques (26).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The intensities of FIV-specific cytotoxic responses by PBMC with or without a brief stimulation with the T-cell mitogen ConA and IL-2 were lower than those reported for PBMC or ConA blasts of HIV-seropositive humans (14,19,22,30,46,48) or SIV-infected primates (26-28). In addition, we were unable to detect cytotoxic T-cell responses in lymphoblasts sampled before 7 weeks postinfection, whereas SIV-specific cytotoxicity mediated by PBMC was detected as early as 2 weeks after infection of macaques (26).…”
Section: Discussioncontrasting
confidence: 55%
“…Therefore the higher levels of lentivirus-specific CTL activity in humans and simians than in cats may be due to a higher frequency of lentivirusreactive CTL precursors in humans and nonhuman primates. Alternatively, the FIV-specific CTL may be directed against antigens other than envelope proteins, since gag-specific CTL precursor populations have not been detected in HIVseronegative individuals (9, 21,22).…”
Section: Discussionmentioning
confidence: 99%
“…However, the present study of 36 HIV‐infected individuals did not shown an association between the levels of HIV specific‐CTL activity and CD4 count, viral load or risk of death. Our results are in agreement with several studies that report no correlation between anti‐HIV CTL activity and CD4 + cells [ 9–12], CD8 + cells [ 13] or disease stage [ 14, 15]. In another study, which included 57 HIV‐1‐infected homosexual men, Rinaldo et al .…”
Section: Discussionsupporting
confidence: 93%
“…All CTL assays were conventional 5-h 51Cr release assays as described in Littaua et al (24) and Koup et al (23). Briefly, autologous and allogeneic B-LCL target cells infected at a multiplicity of infection of 5 to 10 PFU per cell 16 h prior to the assay were 51Cr labeled by incubation of 106 cells with 100 ,uCi of Na" CrO4 (Amersham, Arlington Heights, Ill.) in a 100-pul volume for 1 h at 37°C, washed four times, and resuspended in R10 medium at 105 cells per ml.…”
mentioning
confidence: 99%